Analyzing the Phillips Curve in the Context of Population Growth in Pakistan - Ullah , Sami; Mughal, Khalid Mehmood; Ullah, Ihsan (The Lighthouse Journal of Social Sciences, 2024)
This study investigates the long-term link between unemployment and inflation trade-offs in the context of population and GDP growth rates in Pakistan, utilizing yearly time series data from 1980 to 2020 to assess the Phillips curve. Unemployment is the dependent variable in this study, whereas inflation, GDP growth rate, and population growth rate are independent factors. For the data analysis of the proposed model, the Johansen co-integration technique is used to analyze the long-run co-integration study. The findings of the co-integration analysis show that inflation and GDP growth rate have a significant and negative impact on unemployment, whereas the impact of population growth rate on unemployment is positive and significant, supporting the formulated hypothesis. The findings show that the government and policymakers may devise measures to enhance GDP growth, regulate inflation, and properly manage the country's population growth rate in order to reduce unemployment. Policymakers may establish an appropriate and efficient macroeconomic policy mix.